Antioxidant capacity, polyphenol content and contribution to dietary intake of 52 fruits sold in Spain - Arancha Ruiz-Torralba; Eduardo Jesús Guerra-Hernández; Belen García-Villanova (CyTA - Journal of Food, 2018)
Total antioxidant capacity (TAC) and total polyphenol content (TPC) of 52 fruits sold in Spain were evaluated by FRAP, ABTS, DPPH and Folin-Ciocalteu. For berries, TAC was 9, 17 and 31 times greater than for oranges, bananas and apples, respectively. Consumption of unpeeled fruit increases TAC and TPC by 2.4 times. Oranges contribute most to TAC and TPC (33% and 32% respectively) in the Spanish diet. Oranges, strawberries, tangerines, grapes and bananas account for 76% of the TAC of fruits consumed in Spain. The consumption of fruit in Spain has remained stable for the last eight years, but falls below WHO recommendations for daily intake. Greater consumption of fruits is recommended, to increase TAC and TPC and to reduce the risk of developing chronic disease.